A steady state solver for modelling rotating electromechanical devices exploiting the transformation from time to position domain. (23rd July 2013) - Bernat, Jakub; Kolota, Jakub; Stepien, Slawomir; Sykulski, Jan
SUMMARY The paper presents a study on a novel steady state solver for modelling rotating electromechanical devices. As the new contribution, the transformation of the system from time to position domain is exploited to improve the efficiency of computation. The proposed methodology is well suited to optimizing the current or voltage waveforms to drive the system with an imposed reference torque. To illustrate the technique, a brushless direct current motor is considered. Copyright © 2013 John Wiley & Sons, Ltd.